Urinary IL-18 is associated with arterial stiffness in patients with type 2 diabetes - Shi, Caifeng; He, Aiqin; Wu, Xiaomei; Wang, Lulu; Zhu, Xueting; Jiang, Lei; Yang, Junwei; Zhou, Yang (Frontiers in Endocrinology, 2022)
Objective Diabetic kidney disease (DKD) has been shown to be associated with an excess risk of cardiovascular death. Inflammation has been considered central to T2DM pathophysiology and inflammation markers have been linked to cardiovascular disease (CVD). Serum and urinary IL-18 levels were significantly elevated in patients with type 2 diabetes (T2D); however, whether IL-18 levels are associated with the severity of arterial stiffness remains to be determined. This study examined the relationship of IL-18 levels with pulse wave velocity (PWV) as a reflector for arterial stiffness in T2D patients. Methods A total of 180 participants with T2D who had undergone PWV examination were enrolled. Serum and urinary IL-18 were measured using sandwich ELISA kits. Arterial stiffness was determined by carotid–femoral PWV (cf-PWV) and carotid–radial PWV (cr-PWV). Results Urinary IL-18 levels correlated positively with cf-PWV in T2D patients with DKD (r = 0.418, p < 0.001); however, we found no significant correlation between urinary IL-18 and cf-PWV in diabetic subjects without DKD. Also, we found no significant correlation between urinary IL-18 and cr-PWV in T2D participants with or without DKD. Moreover, the association remained significant when controlling for arterial stiffness risk factors, urinary albumin-to-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR). Cf-PWV was greater in the higher group of urinary IL-18 than in the lower group. Nevertheless, we found no significant correlation between serum IL-18 and cf-PWV in participants with T2D. Conclusion Urinary IL-18 levels appear to be associated with greater cf-PWV, suggesting the link between urinary IL-18 and arterial stiffness in T2D patients.